Assessment of soil and water quality of Barapukuria coal mining site, Dinajpur, Bangladesh - Fardushe, Rowshon Shad; Hoque, Md Mahbubul; Roy, Shimul (Bangladesh Journal of Scientific Research, 2016)
From the field observation it is apparent that the color of coal leached drainage water and the agricultural land water are blackish and slightly blackish respectively, which pollutes surface water and the agricultural land. The study showed the present status of the water quality through analyzing different parameters including color, temperature, pH, EC, DO, TDS, BOD, COD, Cl-, Cu, Zn and Fe as well as the status of soil quality where pH, OC, PO4 -, Cu, Cr and Zn were analyzed. All the water quality parameters (e.g. temperature, pH, EC, TDS, DO, and BOD) were within normal levels but the value of COD was higher, which affects the aquatic environment. The concentration of heavy metals in water varied with Zn > Cu > Cr and in soil the concentration varied with Cu > Cr > Zn. Bangladesh J. Sci. Res. 27(1): 63-73, June-2014